Thursday

April 17, 2014

April 17, 2014

Posted by **Rosilyn** on Saturday, October 8, 2011 at 2:21pm.

Sec^4x - Tan^4x = Sec^2x + Tan^2x

- math -
**Reiny**, Saturday, October 8, 2011 at 4:46pmLS = (sec^2 x - tan^2x)(sec^2x + tan^2x)

= (1 + tan^2x - tan^2x)(sec^2x + tan^2x)

= 1(sec^2x + tan^2x)

= RS

**Related Questions**

math - Prove that the equation Is an identity. Sec^4x - Tan^4x = Sec^2x + Tan^2x

Pre Calculus - Prove that the equation is an identity. sec x/(sec x -tan x)=sec^...

Precalculus - Prove that the equation is an identity. sec x/(sec x -tan x)=sec^2...

Prove trig identity - Prove the following trigonometric identity: (sec^2x-1)(csc...

trig - prove the trig identity cos(4x) = 2-sec^2(2x)/sec^2(2x)

Trig - Prove the trig identity cos(4x)=2-sec^2(2x)/sec^2(2x)

Trig - Prove the trig identity cos(4x)=2-sec^2(2x)/sec^2(2x)

Trigonometry desperate help, clueless girl here - 2. solve cos 2x-3sin x cos 2x...

Trigonometry - 1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two ...

trigonometry hlp me - 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin y...